Ephyrae and metaephyrae of Pelagia noctiluca: stage determination, morphometry and shrinkage. (31st August 2021) - Ottmann, Daniel; Leyva, Laura; Reglero, Patricia; Prieto, Laura; Alvarez, Itziar
Abstract: Understanding processes occurring in the different life stages of jellyfish is key to advance knowledge on their trophic interactions and population dynamics. We describe four developmental stages of Pelagia noctiluca ephyrae and metaephyrae based on the progress of feeding structures and morphometric measurements on the central disc diameter and total body diameter. Size differs significantly among stages, but it can overlap substantially, suggesting that it is not always coupled with development progress due to different somatic growth. Morphological distinction of stages is biologically important because it implies different levels of food specialization and capture efficiency. We further report a 25% (±13 SD) shrinkage of ephyrae and metaephyrae after storage in 4% formaldehyde solution. This metric can be used in ecological studies focusing on size-related traits of field observed individuals.